Attributions of victim responsibility in revenge pornography. Issue 4 (30th October 2019) - Gavin, Jeff; Scott, Adrian J.
Abstract : Purpose: Revenge pornography is a growing risk among adolescents and young adults. Often stemming from sexting, some victims of revenge pornography report experiencing victim-blame similar to that accompanying the reporting of rape. The purpose of this paper is to explore the assumptions that underlie attributions of victim-blame, with a focus on perpetrator and victim responsibility, as well as gendered assumptions surrounding sexting. Design/methodology/approach: A total of 222 UK university students (111 male, 111 females) read one of two versions of a hypothetical revenge pornography scenario, one involving a male victim of a female perpetrator, the other a female victim of a male perpetrator. They then responded to an open-ended question regarding responsibility. Findings: Qualitative content analysis of these responses identified three inter-related themes: the victim's behaviour, mitigating victim responsibility and minimising the behaviour. Social implications: The majority of participants in this study attributed at least some responsibility to the victims of revenge pornography depicted in the scenarios. Sex of the victim played a less important role than assumptions around sexting. Originality/value: The study suggests that victim-blame is linked to the consent implied by sharing intimate images with a partner, but is also mitigated by the normative nature of this relationship practice. There was some evidence that the experience of male victims of revenge pornography is trivialised. These findings have implications for e-safety and victim support.